Pengaruh waktu milling terhadap Sifat mikro struktur dan magnet dari NdFeB dengan proses Wet dan Dry milling - Wahyu Solafide Sipahutar; William Wiliiam; Muljadi Muljadi (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2021)
Making of magnets from NdFeB flakes by Wet and dry milling to determine the microstructure, physical and magnetic properties of the milling time variation is 16, 24, and 48 hours. The milling powder is then analysed to determine the particle size with PSA and XRD to determine the phase formed. Then the compacting process with isotropy printing for making pellet test samples with a pressure of 7 tons for 2 minutes. Then the pellet sample, given annealing temperature with a variation of 150 and 170 ?C, then a measurement of magnetic properties with a Gauss Meter. The results obtained by the smallest optimum particle size with 48 hours of milling time at a diameter of 90% 4.7 ?m, while the results of dry milling at a diameter of 90% amounted to 60.85 ?m. The best method to get the smallest particle size is the Wet milling method. XRD results with Wet and Dry milling phases that appear only Nd2Fe14B phase. As milling time increases, the resulting density increases. The largest magnetic flux testing with dry milling method with 48 hours of milling time for temperatures 170 ?C temperature obtained 468.5 Gauss and the addition of annealing temperature the magnetic properties of the material is getting better.